Women on the move: the mobile phone as a gender technology - Ganito, Carla (2013)
Our lives are increasingly performed within a mobile context. The current trend in Europe and the USA is a balance between men and women in mobile phone usage. Nevertheless usage parity does not mean usage equality. It is mostly ignored that women’s appropriation of the mobile phone is very distinct from men’s, similarly to what happens with other technological objects. Grounding the research in feminist media theory, this paper offers a view of the mobile phone as a technology of gender. I seek to show that the mobile phone contributes to gender construction and transformation. The paper begins with an analysis of the state of the art of feminist media studies. It follows by discussing the mobile phone as a media and its dichotomous position with regards to gender. The paper finalizes with a proposition of the mobile phone as a technology of gender, a place for gender transgression and possible transformation.